Glutamate receptors in domestication and modern human evolution. (January 2020) - O'Rourke, Thomas; Boeckx, Cedric
Highlights: Human and domesticate signals of selection occur on kainate and metabotropic receptor genes. These genes are highly expressed in stress-response regions throughout development. Kainate and metabotropic receptor genes are associated with multiple stress disorders. These receptors attenuate stress responses by modulating excitation of the HPA axis. This attenuation alters prenatal development in both domesticates and modern humans. Abstract: There has been a recent resurgence of interest in the hypothesis that anatomically modern humans and domesticated species have followed convergent evolutionary paths. Here, we review results from domestication and modern-human evolutionary studies in order to evaluate evidence for shared changes to neurotransmission across these species. We compare genomic and, where available, brain-expression differences across 488 neurotransmitter receptor genes in 14 domesticated species and modern humans relative to their wild and archaic counterparts. This analysis highlights prevalent changes to glutamate — most notably kainate and metabotropic — receptor genes. We review evidence for these genes' expression and their respective receptor functions in the central nervous system, as well as phenotypes commonly associated with alterations to them. This evidence suggests an important role for kainate and metabotropic receptors in regulating hypothalamic–pituitary–adrenal axis excitation, and we provide a mechanistic account of their actions in attenuating the stress response. We assess the explanatory potential of such actions in contributing to the emergence of the (self-)domesticated phenotype, in particular to reduced reactive aggression.